Effort Increase Results Study Student on Fikih Subject Using Problem Based Learning (PBL) Method In Class VII MI Miftahul Anwar Kurungrejo Nganjuk Regency - Badrusalim, Mochamad; Tiyas, Naning Sulistyaning; Rosyid, Fathor; Indrioko, Erwin; Mushlihin, Imam Annas (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Classroom action research was carried out because the percentage of student completion was only 59% of students whose scores met the KKM, with the use of Problem Based Learning (PBL) in Fiqh learning it is hoped that it will be able to improve student learning outcomes in accordance with the learning objectives. The formulation of the research problem is how to implement fiqh learning using the PBL method and how to improve student learning outcomes in fiqh lessons using the PBL method at MI Miftahul Anwar Kurungrejo Prambon Nganjuk. This research uses the steps of preparing a plan, taking action, making observations, and doing reflection. The object of this research is MI class VI student Miftahul Anwar in the fiqh subject. The results of classroom action research are the application of the PBL learning method with several stages starting from preparing problems or problems that will be solved by students. The application of the PBL learning method is based on data obtained from cycles I and II. It can be seen that the application of the PBL learning model in Fiqh subjects can improve student learning outcomes. In cycle I the percentage of achieving the minimum completeness criteria was 70.59% and in cycle II the percentage of achieving the minimum completeness criteria was 94.18% > 90% so that with these data it can beconcluded that the success criteria for student learning outcomes research have been achieved.